Lee waves as evidenced by satellite cloud pictures - DE, U. S. (MAUSAM, 1970)
The paper presents the observational evidence of mountain waves in the Indian region with particular reference to the Assam and Burma hills with the help of satellite pictures. In all, sixteen cases have been studied and the observed wavelengths vary between 17-34 km. In all the cases the conditions for formation of mountain waves were found favourable as evidenced by the wind profile and thermal stability of the atmosphere.